Effects of XFE liquid energy and choice white grease on nursery pig performance - W Ying; Joel M DeRouchey; Michael D Tokach; Robert D Goodband; Jim L Nelssen; Steven S Dritz (Kansas Agricultural Experiment Station Research Reports, 2011)
Two experiments were conducted to evaluate the effects of XFE Liquid Energy (XFE Products, Des Moines, IA) and choice white grease (CWG) on growth performance of nursery pigs. In Exp. 1, a total of 150 nursery pigs (TR4 × 1050, initially 27.0 lb) were used in a 21-d experiment. Pens of pigs were balanced by initial BW and randomly allotted to 1 of 5 dietary treatments with 6 replications per treatment. The 5 dietary treatments included a control corn-soybean meal-based diet, the control diet with 2 or 4% CWG, or the control diet with 2 or 4% liquid energy. Overall (d 0 to 21), pigs fed diets containing liquid energy had improved ADG (P<0.02) and ADFI (P<0.04) with no change in F/G compared with control pigs. Pigs fed CWG had greater (P<0.04) ADG and improved (P<0.01) F/G compared with pigs fed the control diet. The responses tended to be linear (P<0.09) for liquid energy and were linear (P<0.05) for CWG. Finally, pigs fed CWG had improved (P<0.02) F/G compared with pigs fed liquid energy.; Swine Day, Manhattan, KS, November 17, 2011
Keywords: Swine Day; 2011; Kansas Agricultural Experiment Station contribution; no. 12-064-S; Report of progress (Kansas State University. Agricultural Experiment Station and Cooperative Extension Service); 1056; Swine; Choice white grease; Liquid energy; Nursery pig